Pervasive Device and Service Discovery Protocol in Interoperability XBee-IP Network - Sabriansyah Rizqika Akbar; Helmi Nizar; Wijaya Kurniawan; Mochammad Hannats Hanafi Ichsan; Issa Arwani (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
The Internet of Things (IoT) communication protocol built over IP and non-IP environment. Therefore, a gateway device will be needed to bridge the IP and non-IP network transparently since an IoT user is more likely to concern on the service provided by the IoT device, rather than the complexity of the network or device configuration. Since today ubiquitous computing needs to hide the architectural level from it users, the data & information centric approach was proposed. However, the data & information centric protocol is having several issues and one of them is device and service discovery protocol over IP & non-IP network. This paper proposed a pervasive device and service discovery protocol that able to work in interoperability of the IP and non-IP network. The system environment consists of a smart device with XBee Communication as the non-IP network that will send the device and service description data to the IP network using WebSocket. The gateway will able to recognize the smart device and sent the data to the web-based user application. The user application displayed the discovered devices along the services and able to send the control data to each of the smart devices. Our proposed protocol also enriched with the smart device inoperability detection by using keep-alive tracking from the gateway to each of the smart devices. The result showed that the delay for the user application to detect the smart device in the XBee network is around 10.13 ms delay, and the service average delay requested by the user application to each of the devices is 2.13 ms.